Lightning performance analysis of a rooftop grid- connected solar photovoltaic without external lightning protection system - Mohd Nasir, Mohd Solehin (2018)
The Sustainable Energy Development Authority of Malaysia (SEDA) received complaints on damaged components and distribution boards of PV systems due to lightning strikes. Permanent and momentary interruptions on distribution circuits may also occur from the disturbance. In this research, a solar PV Rooftop system (3.91 kWp) given by SEDA is modelled in the PSCAD/EMTDC. The Heidler function is used as lightning current waveform model to analyse the transient current and voltage at two different points under the influence of lightning events. These include different lightning current waveshape, standard lightning current and non-standard lightning current. The effect of the system components when lightning direct strikes at two different points of the installation are examined in this study. The two points lies between the inverter and the solar PV array and between inverter and grid. Extremely high current and voltage due to the direct lightning strike on a certain point at PV Rooftop system are also studied. The results of this case study are observed with the inclusion of surge protective devices (SPDs) and without SPDs. The parameters used were 31 kA peak current, 10 meters length of cable and the lightning impulse current waveshape of 8/20μs. The high current and voltage at P1 striking point are 31 kA and 2397 kV, respectively. As for the AC part, the current and voltage values were found to be 5.97 kA and 5392 kV, respectively. Therefore, SPD with suitable rating provided by SEDA were deployed. Results show that high transient current voltage is expected to clamp sharply at the values of 1.915 kV and 0 A at the P1 striking point. As for the AC part, the current and voltage values were found to be 0 kA and 0.751 V, respectively. Varying lightning impulse current waveshapes at striking point P2 showed that the highest voltage was obtained at waveshape 10/350 μsat 11277 kV followed by waveshapes of 2/70 μs, 8/20 μs and 0.7/6 μs. The high value of transient voltage was clamped at a lower level of 2.029 kV. Different lightning amplitudes were also applied, ranging from 2 – 200 kA selected based on the CIGRE distribution. It shows that the current and voltage at P1 and P2 are directly proportional. Therefore, the SPD will be designed at an acceptable rating and proper position of SPD installation at solar PV Rooftop will be proposed. The results obtained in this study can then be utilized to appropriately assign a SPD to protect the PV systems that are connected to the grid. If SPDs are installed without consideration of the concept of lightning protection zones, the equipment to be protected are prone to damage despite the correct energy coordination of SPDs. Therefore, the simulation results serve as a basis for controlling the effects of lightning direct strikes on electrical equipment and power grids. Then provide proper justification on SPD coordination in ensuring the reliability of the system.